Promoting Sustainability through Regional Food and Wine Pairing - Serra, Manuel (2021)
Serra, M., Antonio, N., Henriques, C., & Afonso, C. M. (2021). Promoting Sustainability through Regional Food and Wine Pairing. Sustainability, 13(24), 1-22. [13759]. https://doi.org/10.3390/su132413759